A Transmembrane Histidine Kinase Functions as a pH Sensor - Bortolotti, Ana (Biomolecules, 2020)
The two-component system DesK-DesR regulates the synthesis of unsaturated fatty acids in the soil bacteria Bacillus subtilis. This system is activated at low temperature and maintains membrane lipid fluidity upon temperature variations. Here, we found that DesK—the transmembrane histidine kinase—also responds to pH and studied the mechanism of pH sensing. We propose that a helix linking the transmembrane region with the cytoplasmic catalytic domain is involved in pH sensing. This helix contains several glutamate, lysine, and arginine residues At neutral pH, the linker forms an alpha helix that is stabilized by hydrogen bonds in the i, i + 4 register and thus favors the kinase state. At low pH, protonation of glutamate residues breaks salt bridges, which results in helix destabilization and interruption of signaling. This mechanism inhibits unsaturated fatty acid synthesis and rigidifies the membrane when Bacillus grows in acidic conditions.